ANALISIS POLA TABUHAN KESENIAN ZIKIR MAULID PADA PASAL HABIBUN DI DESA MEKAR SEKUNTUM KECAMATAN TEBAS KABUPATEN SAMBAS - Prabowo Dhanurianto; Nurmila Sari Djau; Yudhistira Oscar Olendo (Universitas Tanjungpura, 2021)
AbstractThe background of the research is to preserve the art of remembrance of the maulid by describing, notating, and analyzing the various patterns of wasps in the art of remembrance of the maulid in the pasal habibun in Mekar Sekuntum Village, Tebas District, Sambas Regency. The purpose of the study is to describe the analysis of the pattern of wasps in the art of remembrance of maulid in the pasal habibun. The method used is descriptive analysis and uses a musicological approach. The research data is in the form of various wasps patterns and analysis of wasps patterns in the art of remembrance maulid. The resource persons in this research are Halimi and Baizuri who play an active role and know about this art. The data collection tool is the researcher as the main instrument and uses auxiliary instruments in the form of observation sheets and interview guidelines. The data analysis technique analysis techniques. he results showed that there were five kinds of wasp patterns used, namely the Tanjidor, 2:1/Keroncong, Sorong Dayung, Gantung, Shalawat. The research is expected to stimulate the growth of interest in studying traditional arts.Keywords: Analysis, Wasp pattern ,Maulid recitation, Pasal Habibun.